Multibacillary Leprosy With Tumor Like Nasal Deformity - Lubis, Ramona Dumasari; Darmi, Mila; Dewi, Nani Kumala (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Leprosy is a chronic granulomatous infection caused by Mycobacterium leprae which affects skin, peripheral nerves, and other body parts including bone, ear, eye, and nose. Nasal manifestation of leprosy may be found in the early stage with non-specific symptoms such as nasal congestion. In advanced stage, destruction of bone structures and cartilages may result in deformities. However, nasal manifestation as the only symptom in early stage can lead to delayed diagnosis. CASE REPORT: We reported a case of multibacillary leprosy in a 26-year-old male with tumor like nasal deformity for 1 year and lump in the ear lobes since 8 years ago. Initially, there was nasal discharge, unfrequent epistaxis, followed by loss of smelling perception, without associated pain, or numbness since childhood. Lesions on the trunk, palms, and soles were also noted since 2 years ago. The physical examination revealed tumor with crusts and fissures on the nasal tip; accompanied by saddle nose. Slit skin smear revealed acid-fast bacilli with bacteriological index of 4+ in solid form. Hence, he was diagnosed as multibacillary leprosy with Grade 2 disability. The prognosis was poor due to permanent deformities. CONCLUSION: Early diagnosis and initiation of treatment are crucial in the management of this debilitating and stigmatized disease.